Patterns of post-traumatic stress symptoms in mild traumatic brain injury and their relationship with outcomes: a latent profile analysis. - Faulkner JW; Snell DL; Theadom A; de Terte I; Low R (Taylor and Francis Group, 2023)
INTRODUCTION: Post-traumatic stress symptoms (PTSS) are known to contribute to postconcussion symptoms and functional status following mild traumatic brain injury (mTBI). Identifying symptom cluster profiles provide an opportunity to better understand PTSS and their influence on these outcomes. In this study, latent profiles of PTSS following mTBI were identified, and their association with mTBI outcomes was examined. The predictive role of demographic and injury related variables on profile membership was also explored. METHOD: Adults (N = 252) completed self report measures of PTSS and mTBI outcomes (post-concussion symptoms and functional status) within three months of mTBI. These measures were re-administered six months later (N = 187). Latent profile analysis (LPA) was used to ascertain the latent class structure of PTSS, and regression analysis to examine predictors of profiles. ANCOVA, with general psychological distress as a covariate, revealed the relationship between profiles and mTBI outcomes. RESULTS: LPA identified a four-profile model to best describe PTSS at baseline. This included a resilient (49.6%), moderate (30.6%), moderate with high intrusion/avoidance (14.3%) and a highly symptomatic profile (5.6%). A secondary school education or less and/or unemployment before mTBI was significantly more likely in the highly symptomatic profile, as well as sustaining an mTBI due to an assault or motor vehicle accident. PTSS latent class membership was significantly associated with mTBI outcomes even when controlling for general psychological distress. The resilient group had significantly better outcomes at baseline and six-month follow-up. However, no significant differences in mTBI outcomes emerged between the moderate, moderate with high intrusion/avoidance and the highly symptomatic profiles. CONCLUSION: The current study provides novel information on the symptom profiles of PTSS in mTBI, predictors of profile membership and their relationship with mTBI outcomes. Although future research using this approach is needed, the current study offers a more in-depth understanding of PTSS in mTBI to inform clinical care.
Keywords: Mild traumatic brain injury; latent profile analysis; outcomes; post-traumatic stress; Adult; Humans; Brain Concussion; Stress Disorders, Post-Traumatic; Post-Concussion Syndrome; Schools